P-374 Serum progesterone levels on the of embryo transfer in replacement cycles (HRT-ET): soft capsules vs suppositories may make a difference. (30th June 2022) - Kohls Ilgner, G; Cerrillo, M; Pacheco, A; Cruz, M; Toribio, M; García-Velasco, J.A
Abstract: Study question: Are there differences in serum progesterone levels when vaginal progesterone is administered in soft capsules vs suppositories in HRT-ET? Summary answer: Mean serum levels of progesterone in embryo replacement cycles are higher when progesterone suppositories are used instead of soft capsules. What is known already: Serum levels of progesterone on the day of the embryo transfer has captured recent attention, as it may vary among patients and different vaginal progesterone formulations. Previous studies have suggested that natural micronized vaginal progesterone induces a comparable decidual transformation and clinical pregnancy rates to vaginal progesterone gel. However, no data exists comparing suppositories versus soft capsules. Study design, size, duration: Prospective, observational, single center study to compare serum progesterone levels on the day of the embryo transfer in women undergoing HRT-ET and being treated with vaginal progesterone in capsules or suppositories. Also, a patient satisfaction questionnaire was given to women participating in the study to investigate patient experience. Sample size calculation estimated 50 patients per group needed for a = 0.05 and power 90%, considering standard deviation of 5.1. Participants/materials, setting, methods: From April to October 2021, 100 patients undergoing HRT-ET were recruited. Only one type of progesterone was administered. 50 patients received soft capsules (Progeffik©, Utrogestan©) and the other half suppositories (Cyclogest©). After estradiol priming for 10-12 days and once confirmed that endometrial thickness was >7mm, 400 mg vaginal progesterone was started b.i.d. Blood was drawn on the day of embryo transfer by venipuncture and progesterone levels in blood were evaluated. Main results and the role of chance: Mean serum levels of progesterone were significantly higher when suppositories were compared with soft capsules (16.2 ± 7 vs 12.5 ± 5.2 ng/ml, p = 0.0034). According to our previous studies we considered an adequate cut-off of progesterone of 8.8 ng/ml, and patients with a suboptimal serum level of progesterone were supplemented with subcutaneous progesterone. Of those patients receiving suppositories, only 6 out 50 (12%) required subcutaneous supplementation, whereas it was needed in 12 out of 50 (24%) women receiving soft capsules. No differences were observed in pregnancy rate (70% vs 50%) or ongoing pregnancy rate (48% vs 36%). Regarding patient satisfaction, no differences were observed in the frequency of itching, burning, leakage of medication or drowsiness between groups. Limitations, reasons for caution: We should consider the limited sample size and the study design, not randomized, before generalizing the results observed. Wider implications of the findings: In luteal support of frozen embryo replacement cycles, vaginal progesterone suppositories yields superior progesterone serum levels than soft capsules. Trial registration number: Not applicable